2009
DOI: 10.1111/j.1751-2980.2008.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease: A survey of the epidemiology in Asia

Abstract: Inflammatory bowel disease (IBD) has long been considered a disease that affects predominantly a Western population. The incidence and prevalence rates from Asian populations are much lower in comparison. More recent data, however, have shown significantly higher rates in Asians and time trend studies have shown an increase in the incidence of ulcerative colitis (UC) and a similar but lower rise in Crohn's disease (CD). The epidemiological changes that are taking place mirror that of the Western experience see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 40 publications
5
98
0
1
Order By: Relevance
“…38 Total Parenteral Beslenme İBH'de total parenteral beslenme, özellikle atak döneminde olan hastaların barsak istirahatinin ve gelişen besin ögesi yetersizliklerinin sağlanması için uygulanabilir. 39 Ayrıca, malnütrisyon İBH hastalarında sıklıkla ortaya çıkan bir durumdur. Bu durumu engellemek için de total parenteral beslenme bu hastalarda uygulanabilir.…”
Section: Enteral Beslenmeunclassified
“…38 Total Parenteral Beslenme İBH'de total parenteral beslenme, özellikle atak döneminde olan hastaların barsak istirahatinin ve gelişen besin ögesi yetersizliklerinin sağlanması için uygulanabilir. 39 Ayrıca, malnütrisyon İBH hastalarında sıklıkla ortaya çıkan bir durumdur. Bu durumu engellemek için de total parenteral beslenme bu hastalarda uygulanabilir.…”
Section: Enteral Beslenmeunclassified
“…These regional differences illustrate the importance of environmental factors in the development of UC. Interestingly, recent reports from Asia, where IBD was previously considered to be rare, have shown increasing rates of UC (more so than with CD) (Goh and Xiao 2009). This pattern of differing rates across the globe also illustrates the importance of environmental factors.…”
Section: Epidemiology Of Uc In Children and Adolescentsmentioning
confidence: 99%
“…The authors found a higher prevalence of IBD (including CD) among children with Middle East ancestry compared to a non-Middle Eastern control group [47] . It should be considered that increased awareness of health professionals and the public to the disease may have contributed to the reported increasing incidence and prevalence of the disease [34] .…”
Section: Alhagamhmad Mh Et Al Epidemiology Of Crohn Diseasementioning
confidence: 99%
“…The changing diet habits of Asian populations is one factor that may be responsible for the rising incidence [34,51] . A multicentre case-control study in Japan found that a higher consumption of refined sugars and a high fat diet correlated with the increase in newly diagnosed cases of CD in that country [52] .…”
Section: Role Of Environmental Factors In CD Pathogenesis and Changinmentioning
confidence: 99%
See 1 more Smart Citation